Nonlinear asset pricing in Chinese stock market: a deep learning approach - Pan, Shuiyang; Long, Suwan (Cheng) (Elsevier, 2023)
The redesign of asset pricing models failed to integrate the frequent financial phenomenon that stock markets exhibit a non-linear long- and short-term memory structure. The difficulty lies in developing a nonlinear pricing structure capable of depicting the memory influence of the pricing variable. This paper presents a Long- and Short-Term Memory Neural Network Model (LSTM) to capture the non-linear pricing structure among five elements in the Chinese stock market, including market portfolio return, market capitalization, book-to-market ratio, earnings factor, and investment factor. The long-short-term memory structure implies that the autocorrelation function of the stock return series decays slowly and has a long-term characteristic. The LSTM model surpasses the standard Fama–French five-factor model in terms of out-of-sample goodness-of-fit and long-short strategy performance. The empirical findings indicate that the LSTM nonlinear model properly represents the nonlinear relationships between the five components.
Keywords: Nonlinear asset pricing; Long short-term memory neural network; Deep learning